Optimalisasi manajemen strategi: peningkatan loyalitas nasabah bank syariah di era digital - Ningrum, Ajeng Rizqi (Maliki Interdisciplinary Journal, 2025)
The current development of digital technology requires Islamic banks to adapt by managing their strategies more effectively to maintain and increase customer loyalty. This research focuses on how the right strategies can help Islamic banks navigate the digital era optimally. Based on the study’s findings, the use of digital services such as mobile banking, Sharia-compliant digital networks, and blockchain technology has been shown to create faster, easier, and more convenient services for customers. This directly impacts customer satisfaction and trust, ultimately strengthening their loyalty to the bank. Digital marketing strategies are also key to attracting the public, especially the younger generation. The use of social media, creative promotions, collaboration with influencers, and educational programs on Islamic finance have proven effective in increasing engagement and maintaining long-term relationships with customers. In addition to service innovation, factors such as service quality, compliance with Sharia principles, and product excellence also play a significant role in building customer trust and strengthening their loyalty.